Behavioural recovery after treatment for varicose veins. Issue 4 (25th January 2016) - Cotton, S C; MacLennan, G; Brittenden, J; Prior, M; Francis, J
Abstract: Background: The aim of this study was to assess behavioural recovery from the patient's perspective as a prespecified secondary outcome in a multicentre parallel-group randomized clinical trial comparing ultrasound-guided foam sclerotherapy (UGFS), endovenous laser ablation (EVLA) and surgery for the treatment of primary varicose veins. Methods: Participants were recruited from 11 UK sites as part of the CLASS trial, a randomized trial of UGFS, EVLA or surgery for varicose veins. Patients were followed up 6 weeks after treatment and asked to complete the Behavioural Recovery After treatment for Varicose Veins (BRAVVO) questionnaire. This is a 15-item instrument that covers eight activity behaviours (tasks or actions an individual is capable of doing in an idealized situation) and seven participation behaviours (what the individual does in an everyday, real-world situation) that were identified to be important from the patient's perspective. Results: A total of 798 participants were recruited. Both UGFS and EVLA resulted in a significantly quicker recovery compared with surgery for 13 of the 15 behaviours assessed. UGFS was superior to EVLA in terms of return to full-time work (hazard ratio 1·43, 95 per cent c.i. 1·11 to 1·85), looking after children (1·45, 1·04 to 2·02) and walks of short (1·48, 1·19 to 1·84) and longer (1·32, 1·05 to 1·66) duration. Conclusion: Both UGFS and EVLA resulted in more rapid recovery than surgery, and UGFS was superior to EVLA for one-quarter of the behaviours assessed. The BRAVVO questionnaire has the potential to provide important meaningful information to patients about their early recovery and what they may expect to be able to achieve after treatment. Abstract : BRAVVO questionnaire provides important recovery information